Stable determination of an inclusion for a class of anisotropic conductivities. (1st August 2017) - Di Cristo, Michele; Ren, Yong
Abstract: We deal with the inverse problem of determining an inclusion within an electrical conductor from electrostatic boundary measurements. We consider an anisotropic conductivity and provide logarithmic type stability.